2000
DOI: 10.1046/j.1365-8711.2000.03065.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the optical counterpart of the proposed double degenerate polar RX J1914+24

Abstract: We have detected the optical counterpart of the proposed double degenerate polar RX J1914124. The I-band light curve is modulated on the 9.5-min period seen in X-rays. There is no evidence for any other periods. No significant modulation is seen in J. The infrared colours of RX J1914124 are not consistent with a main-sequence dwarf secondary star. Our ASCA spectrum of RX J1914124 is typical of a heavily absorbed polar and our ASCA light curve also shows only the 9.5-min period. We find that the folded I band a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
110
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(122 citation statements)
references
References 38 publications
12
110
0
Order By: Relevance
“…The same was found in the optical by Ramsay et al (2000). A similar analysis of RX J0806.3+1527 X-ray data by Israel et al (1999) and optical data by Israel et al (2002) and Ramsay et al (2002a) also found only one period with its harmonics (but see below for further discussions).…”
Section: Frequency Analysis Of Light Curvessupporting
confidence: 73%
See 4 more Smart Citations
“…The same was found in the optical by Ramsay et al (2000). A similar analysis of RX J0806.3+1527 X-ray data by Israel et al (1999) and optical data by Israel et al (2002) and Ramsay et al (2002a) also found only one period with its harmonics (but see below for further discussions).…”
Section: Frequency Analysis Of Light Curvessupporting
confidence: 73%
“…No hard component was evident in the ROSATdata (Motch & Haberl 1995). Much deeper hard X-ray observations of RX J1914.4+2456 were carried out by Ramsay et al (2000) with ASCA: they measured an upper limit of the bolometric luminosity of this component of 10~7 with respect to the terms of use, available at https://www.cambridge.org/core/terms. https://doi.org/10.1017/S0252921100002281 …”
Section: X-ray Spectrummentioning
confidence: 99%
See 3 more Smart Citations